A thinner endometrium is associated with a greater risk of preterm delivery after fresh cleavage embryo transfer but not after blastocyst transfer: a retrospective cohort study of 11,111 singleton live births - Ye, Tian; Kong, Huijuan; Bu, Zhiqin; Fan, Wenqian; Du, Linqing; Li, Jing; Guo, Yihong (Frontiers in Endocrinology, 2025)
BackgroundEndometrial thickness (EMT) has been confirmed to be associated with pregnancy outcomes after in vitro fertilization/intracytoplasmic sperm injection-embryo transfer (IVF/ICSI-ET), but studies on its relationship with neonatal outcomes are still limited. To our knowledge, this study is the first to investigate the relationship between EMT on the day of hCG trigger and the risk of preterm delivery (PTD) in populations undergoing cleavage-stage embryo transfer and blastocyst transfer, respectively.MethodsThis study was a retrospective cohort study that included singleton live birth cycles of women who underwent autologous IVF/ICSI-ET at the Reproductive Medicine Center of the First Affiliated Hospital of Zhengzhou University from January 2016 to December 2023. The main study outcome was PTD. The relationship between EMT and PTD was explored using logistic regression in different models. These models were adjusted for baseline characteristics, cycle treatment parameters and maternal pregnancy complications among populations undergoing cleavage-stage embryo and blastocyst transfer.ResultsIn both the unadjusted model and Model I, which was adjusted for baseline characteristics, compared with that in the EMT 7.5–12 mm group, the risk of PTD was significantly greater in the EMT < 7.5 mm group and significantly lower in the EMT ≥ 12 mm group (P < 0.05). In Model II, which was adjusted for all potential confounding factors, including pregnancy conditions, an EMT ≥ 12 mm retained its independent protective effect against PTD in both populations. In contrast, an EMT < 7.5 mm and PTD (OR 2.19; 95% CI, 0.82–5.88; P = 0.118) did not significantly correlated in the blastocyst transfer population. However, in patients undergoing cleavage-stage embryo transfer, an EMT < 7.5 mm remained an independent risk factor for PTD (OR 2.14; 95% CI, 1.09–4.21; P = 0.027).ConclusionsA thin endometrium on the day of hCG trigger is independently associated with an increased risk of PTD in patients undergoing cleavage-stage embryo transfer but not in those undergoing blastocyst transfer. In contrast, a thick endometrium significantly reduces the risk of PTD in both populations.